A qualitative study of transgender individuals' experiences of healthcare including radiology. Issue 2 (May 2020) - Floyd, M.J.; Martin, O.; Eckloff, K.J.
Abstract: Introduction: Transgender and gender non-conforming people have historically been hidden in society. Increasing visibility has led to an awareness of the systematic discrimination experienced by this community. Transgender people experience factors that increase their need for healthcare while experiencing a lack of trans appropriate care. The aim of the research was to identify the lived experiences of transgender individuals in accessing radiology Methods: A qualitative approach was used to determine the lived experiences of transgender individuals in accessing radiology for care unrelated to their transition process. In depth semi-structured interviews were used to collect data from six participants who identified as transgender or gender non-conforming. Participants were recruited by personal connection and subsequent snowball style sampling. Systematic thematic analysis was applied to the recorded interviews from each participant Results: Thematic analysis identified a diverse range of individual lived experiences with 3 themes and a series of sub themes: (1) cultural competence (2) social stigma and (3) environment Conclusion: The study findings identify that negative healthcare experiences of transgender individuals are often the result of a lack of transgender knowledge demonstrated by healthcare professionals. Positive healthcare experiences were characterised by the use of inclusive language and the provision of an inclusive environment. Implications for practice: Improving the lived experience of healthcare for transgender individuals will require an improved inclusive curriculum within undergraduate education, as well as post qualification for all healthcare professionals. Healthcare professionals, including radiographers may make immediate improvements in the adoption of a more inclusive language and the display of signs and symbols which reflect a supportive environment. Longer term environmental improvements may include increasing access to gender neutral restrooms and changing facilities